PERFORMANCE OF QUAILS (Coturnix-coturnix japonica) GIVEN DRINK CONTAINING MORINGA LEAF SOLUTION IN THEIR GROWING PERIOD - Rohman, Fatkur; Handarini, Ristika; nur, Hanafi (Jurnal Peternakan Nusantara, 2019)
Moringa leaves contain phytochemicals which can be used to improve the performance of quails in their growing period. This study was aimed at assessing the effects of the inclusion of moringa leaf solution in drinking water on the performance of quails. The study was conducted at Badrupuyuh Farm, Sukajaya Village RT 01/02, Ciomas, Bogor Regency from October to December 2017. One-hundred quail birds aged 7 days with average initial body weight of 17.87±0.46 g were used. The birds were fed starter and grower commercial rations. Moringa leaf solution was given through drinking water. A completely randomized design with 4 treatments and 5 replicates was used. Treatments consisted of drinking water containing no moringa leaf solution (R0), drinking water containing 5% moringa leaf solution (R1), drinking water containing 10% moringa leaf solution (R2), drinking water containing 15% moringa leaf solution (R3). Data were subjected to an analysis of variance and a Duncan test. Measurements were taken on feed intake, body weight gain (BWG), feed conversion, and mortality rate. Results showed that there were significant effects (P<0.05) of treatments on BWG in week 2 and 4 and feed conversion in week 2. No mortality of quails was found. It was concluded that the inclusion of 10% moringa leaf solution in drinking water could increase BWG in week 2 and 4, improve feed conversion, and maintain the life of quails. It was recommended that further studies on the effects of moringa leaf solution inclusion in drinking water on egg production in laying period. Key words: performance, quail, moringa leaf solution